Marning Siung Mas Kediri MSME Success Strategy in Improving Employee Performance through Competency and HR Development - Kristanti, Desi; Churiyah, Madziatul (JEM17: Jurnal Ekonomi Manajemen, 2024)
The influence of competency and human resource (HR) development on employee performance at UMKM Marning Siung Mas Kediri. The aim of this research is to identify the relationship between competency and HR development and employee performance. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with MSME management and employees as well as direct observation. The research results show that competency and HR development have an important role in improving employee performance. Targeted human resource development improves employees' abilities in carrying out their duties, while job-relevant competencies make a significant contribution to individual and organizational performance as a whole. The managerial implication of this research is the importance of investing in competency and human resource development to improve employee performance in MSMEs. Keywords: Competence, HR development, employee performance